Metal-based particles in human amniotic fluids of fetuses with normal karyotype and congenital malformation--a pilot study - Barošová, H; Dvořáčková, J; Motyka, O; Kutláková, K Mamulová; Peikertová, P; Rak, J; Bielniková, H; Kukutschová, J (Environmental science and pollution research international, 2015)
This study explores the inorganic composition of amniotic fluid in healthy human fetuses and fetuses with congenital malformation with a special attention to presence of metal-based solid particles. Amniotic fluid originates from maternal blood and provides fetus mechanical protection and nutrients. In spite of this crucial role, the environmental impact on the composition of amniotic fluid remains poorly studied. The samples of human amniotic fluids were obtained by amniocentesis, including both healthy pregnancies and those with congenital malformations. The samples were analysed using several techniques, including Raman microspectroscopy, scanning electron microscopy with energy-dispersed spectrometry (SEM-EDS), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis. Several metal-based particles containing barium, titanium, iron, and other elements were detected by SEM-EDS and Raman microspectroscopy. XRD analysis detected only sodium chloride as the main component of all amniotic fluid samples. Infrared spectroscopy detected protein-like organic components. Majority of particles were in form of agglomerates up to tens of micrometres in size, consisting of mainly submicron particles. By statistical analysis (multiple correspondence analysis), it was observed that groups of healthy and diagnosed fetuses form two separate groups and therefore, qualitative differences in chemical composition may have distinct biological impact. Overall, our results suggest that metal-based nanosized pollutants penetrate into the amniotic fluid and may affect human fetuses.
Keywords: vrozené vady; plod; Female; Amniocentesis; ženské pohlaví; Microscopy, Electron, Scanning; Metals; lidé; mikroskopie elektronová rastrovací; Fetus; Pilot Projects; Spectroscopy, Fourier Transform Infrared; těhotenství; Congenital Abnormalities; pilotní projekty; kovy; studie případů a kontrol; karyotyp; spektroskopie infračervená s Fourierovou transformací; X-Ray Diffraction; amniocentéza; Case-Control Studies; difrakce rentgenového záření; Amniotic Fluid; plodová voda; Karyotype; Pregnancy; Humans